INTERACTIVE MOBILE LEARNING MEDIA TO IMPROVE STUDENTS' HOTS ABILITY SUPPORTED WITH PROBLEM-BASED LEARNING MODEL - Yeni Rima Liana; Suharto Linuwih; Sulhadi Sulhadi (Universitas Negeri Medan, 2020)
Education in the 21st century has entered the era of smartphone technology. The purpose of this research was to test the feasibility and the effectiveness of interactive mobile learning media supported with problem-based learning model to improve students’ HOTS ability. The research and development (R & D) with a 4D model (Define, Design, Develop, Disseminate). The field testing was a quasi-experiment with a pretest and posttest control group design. The research subjects consisted of four lecturers as expert validators, two teachers and two groups of 72 students in a senior high school 2 Batang Regency, Central Java. Data collection techniques through questionnaires, observation, interviews, and written test. Product feasibility test by material experts get a score of 3.65, media experts with a score of 3.68 and student responses with a score 3.46 all in very good category. The results of the Normalized-gain test were 70.60 for the experiment group and 35.69 for the control group. This shows that there were differences in the increase of students' HOTS ability between the experiment group and the control group. Based on the results of the Multivariate Test on GLM with partial eta squared, it was found that this media made an effective contribution of 88.5% to improving students' HOTS abilities